Patterns of Third Molar Impaction among Patients in the Faculty of Dentistry at a University Teaching Hospital. - Bunyarit, Safar Sumit Bunyarit; Aripe, Ernih Mohd; Arif, Shahirah (Japan International Cultural Exchange Foundation, 2024)
Background: Third molars are the most common teeth that may follow an abortive eruption path and become impacted. Aim of study: To analyze the pattern of third molar impaction in ethnic groups in the Faculty of Dentistry in a University teaching hospital. Materials and Methods: A total of 680 panoramic radiograph films of patients aged 18-35 years old, were examined. Patients were from major ethnic groups like Malay, Chinese and Indian, who had minor oral surgery for third molar removal. The angle and depth of impaction were recorded for the surgically removed impacted third molars. Analysis was carried out using SPSS statistical package-version 16.0. Appropriate statistical tests of association were conducted using the Pearson y; test. Results: The frequency of impacted molars was higher in the mandible (661/680 = 97%) than in the maxilla (19/680 = 3%). The mesioangular impaction was most common in the Malay population (33.9%) while horizontal impaction was the most common among Indians (54.1%) and Chinese (39.5%). The distribution of different angulation of impaction was significantly different between sexes (P < 0.05). The proportion of the different levels of impaction was significantly different in two arches (P < 0.05). There was also significant relationship between the level of impaction and sex. Conclusions: Mesioangular impacted third molar was the most common and the easiest one to be removed. In the Malay population, mesioangular impaction was the most common, while horizontal impaction was most common among the Chinese and Indian populations. The results depict that the level and type of impaction directly reflects on the difficulty and complications encountered during surgical removal.